The quality life in patients with chronic obstructive pulmonary disease combined with arterial hypertension - I. M. Fushtey; S. L. Podsevahina; O. V. Tkachenko; A. I. Palamarchuk; E. S. Cabanna (Сучасні медичні технології)
Purpose of the study. Was to investigate life quality in patients with comorbidly pathology of chronic obstructive pulmonary disease in combination with arterial hypertension.